Dampak Fatherless Terhadap Kemampuan Komunikasi Anak Usia 5 - 6 Tahun - Gita, Milda Sahara; Parapat, Asmidar (Universitas Pahlawan Tuanku Tambusai, 2024)
In this study, the researcher explores the condition of fatherlessness in Indonesia, ranking it as the third fatherless country in the world. Factors such as traditional gender culture, patrilineal patterns, and high divorce rates or parental busyness contribute to this situation. The impact of fatherlessness on children aged 5-6 includes difficulties in managing emotions and limitations in communication development, such as language skills, vocabulary deficits, and an increased risk of externalizing behaviors.